2018
DOI: 10.1590/1518-8345.2888.3094
|View full text |Cite
|
Sign up to set email alerts
|

Cupping therapy and chronic back pain: systematic review and meta-analysis

Abstract: Objectives:to evaluate the evidence from the literature regarding the effects of cupping therapy on chronic back pain in adults, the most used outcomes to evaluate this condition, the protocol used to apply the intervention and to investigate the effectiveness of cupping therapy on the intensity of chronic back pain. Method:systematic review and meta-analysis carried out by two independent researchers in national and international databases. Reference lists of systematic reviews were also explored. The quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 48 publications
(187 reference statements)
2
41
1
12
Order By: Relevance
“…Regarding the change in the muscular strength of the trunk extensors of individuals who have reported low back pain, it can be related to changes in neural adaptation and the consequent modification in motor control due to chronic pain (25) , which can generate functional limitations, and consequent limitation in activities of daily living (26) .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the change in the muscular strength of the trunk extensors of individuals who have reported low back pain, it can be related to changes in neural adaptation and the consequent modification in motor control due to chronic pain (25) , which can generate functional limitations, and consequent limitation in activities of daily living (26) .…”
Section: Discussionmentioning
confidence: 99%
“…Cupping therapy has been used for a long time for both acute and chronic low back pain. Studies have shown significant reduction in pain intensity scores and improvement in functional outcome tools with cupping compared to other modalities of treatment like usual care or medications [34,35]. Wang et al conducted a meta-analysis of six randomized controlled trials (RCTs).…”
Section: Low Back Painmentioning
confidence: 99%
“…78 Kronik bel ağrısında kupa tedavisinin etkinliğini değerlendiren 10 çalışmanın metaanalizinde, kupa tedavisinin ağrı yoğunluğu skorunu istatistiksel olarak anlamlı (p<0,01) şekilde düşürdüğü bulunmuştur. 79 OSTEOARTRİT Diz osteoartritinde kuru kupa tedavisinin etkililiğini araştıran 3 randomize kontrollü çalışmanın (271 hasta) metaanalizinde, farmakoterapi (selekoksib veya parasetamol) ve kuru kupa tedavisinin kombinasyonu ile sadece farmakoterapi karşılaştırıldığında, farmakoterapi ve kuru kupa tedavisinin kombinasyonunun ağrı, sertlik ve fiziksel fonksiyonlarda anlamlı (p<0,01) iyileşme sağladığı ileri sürülmüştür. 80 Diz osteoartritinde kupa tedavisi ile oral asetaminofenin etkililiğini araştıran bir randomize kontrollü klinik çalışmada, hastaların bir bölümüne 0-6. gün, 9-11. gün ve 14. gün olmak üzere toplam 11 seans kupa tedavisi uygulanırken; diğerlerine günde 3 kere 650 mg oral asetaminofen verilmiştir.…”
Section: Bel Ağrisiunclassified